DIALEKTIKA EKSENTRIK GIBRAN DALAM DEBAT PILPRES 2024 (SEBUAH PENDEKATAN HERMENEUTIKA JACQUES DERRIDA) - Deviana, Adella; Indah, Astrid (Sulesana, 2025)
This research examines Gibran's style of using gimmicks, unusual technical terms, and provocative gestures, which can be interpreted as a practice of deconstruction. He systematically undermines traditional binary oppositions such as "substance vs. gimmicks" and "ethical vs. unethical" through questions like "greenflation" and on-stage gestures. This creates tensions of meaning. Furthermore, this communication style has a significant impact on public perception, triggering strong polarization. Gibran successfully cultivated an image as a confident representative of "youth," but he also drew criticism for being condescending to opponents and lacking substance. This divided public perception demonstrates that deconstruction has shifted the focus from the substance of the debate to style and performance. The research used was qualitative, employing Jacques Derrida's deconstruction approach. This approach is descriptive and emphasizes the analysis of processes and the meanings behind them. The theory used serves as a guide to ensure the research remains relevant to the realities on the ground. Data were collected from video and article analysis of the 2024 Presidential Election debates, as well as from literature discussing Jacques Derrida's hermeneutic theory of deconstruction and previous research on political communication. The implications of this research can be concluded that Gibran's eccentric communication style has had a broader impact on political dynamics in Indonesia. His style challenges long-established structures of authority and hierarchy among the political elite, opening up space for unconventional forms of communication. This phenomenon signals a shift in how politicians compete and interact with the public, where unique "political branding" has become as important as track record. However, this also raises important questions about the health of democracy: whether a political style that prioritizes gimmicks and performance will erode the substance of debate and ultimately undermine ethical political values.